Fabrication of Noncytotoxic Functional Siloxane-Coated Bacterial Cellulose Nanocrystals - Lima, Lais R.; Conte, Gabriela V.; Brandão, Larissa R.; Sábio, Rafael M. [UNESP]; De Menezes, Alan S.; Resende, Flávia Aparecida; Caiut, José M. A.; Ribeiro, Sidney J. L. [UNESP]; Otoni, Caio G.; Alcântara, Ana C. S.; Barud, Hernane Da S. (American Chemical Society (ACS), 2022)
Bacterial cellulose nanocrystals (BCNC) stand out as versatile biocolloidal building blocks for materials that are high-performance, owing to their inherently high crystallinity and specific modulus and surface area, and sustainable, as BCNC are both biobased and biodegradable. BCNC materials are also promising for their multifunctionality because of their huge potential to undergo physical and/or chemical surface modification. This is particularly appealing for biomedical applications thanks to the biocompatibility, high purity, and low toxicity of BCNC. We report on films based on surface-modified BCNC with varying contents of 3-glycidyloxypropyltrimethoxysilane (GPTMS) or 3-aminopropyltriethoxysilane (APTS). Importantly, these highly pure and crystalline needle-shaped BCNC were isolated from scraps generated at industrial operations when shaping bacterial cellulose membranes into wound dressings. The films were extensively characterized as far as their structural characteristics, with emphasis on the major features targeting at biological applications. Compared with pristine BCNC, the films performed better from the thermal stability standpoint and maintained the noncytotoxicity against nontransforming fibroblasts. The latter claim was independent of GPTMS content, but dose-dependent for APTS and valid for films containing up to 30% of this coupling agent. Altogether, this contribution expands the wingspan of nanocellulose-based materials in biomedical applications while mitigating the waste of natural resources by upcycling an industrial byproduct, falling within the circular bioeconomy framework.
Keywords: biocellulose; cellulose nanowhiskers; hybrids; microbial cellulose; siloxanes; upcycling